Alat Feeding Ayam Otomatis Berbasis Arduino - Tesar Kornelius; Mohammad Dahlan; Noor Yulita Dwi Setyaningsih (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The increasing population in Indonesia has resulted in increased food needs. One of the factors that affects chicken production is the management of the feeding system. The purpose of this study is to design and create an automatic chicken feeder based on Arduino. Calibrate the Load Cell Sensor. Control the AC motor as a metal screw driver for feeding with a load cell sensor. Determine the amount of chicken feed according to the specified setting point and Connect the MCU Node to the telegram. This study uses the